E-Government, Managerial Staff Preparation and Cognitive Society - Ihar Ivanavich Hancharonak (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the context of E-Government and cognitive society development the necessity of managerial staff with new professional competencies preparation within innovative educational programs is actualized.